Article RETRACTED: include references that are unrelated to the subject of the article and/or the context in which they are cited Estilos de Vida Físicamente Activos en el Contexto Escolar: Aspectos Morfo-Fisiológicos y Funcionales (Physically Active Lifestyles within the School context: Morpho-Physiological and Functional Aspects): Article RETRACTED: include references that are unrelated to the subject of the article and/or the context in which they are cited - Tafuri, Francesco; Martinez-Roig, Rosabel; Susanto, Nugroho; Setyawan, Hendra; Latino, Francesca (Retos, 2024)
La escuela encarna el entorno óptimo para educar a los niños hacia la adopción de estilos de vida activos, que se consideran no solo en términos de salud física sino también desde un punto de vista psicopedagógico y social. La necesidad de integrar la actividad física en la rutina escolar, particularmente en la educación primaria, donde las conductas se establecen y se llevan a etapas posteriores de la vida, es evidente en la literatura científica. Los servicios médicos de la escuela pueden apoyar la organización de sesiones de educación para la salud dirigidas a los estudiantes, con un enfoque en las medidas preventivas. Es imperativo dentro de las prácticas educativas ver el dominio motor como un instrumento crucial para inculcar estilos de vida adecuados, mejorar el crecimiento cognitivo, fomentar la inclusión y abordar los aspectos psicoemocionales y sociorelacionales. La escuela puede contribuir significativamente sirviendo como un entorno fundamental para promover la actividad física a lo largo de varios períodos del día, como la incorporación del movimiento en la enseñanza, los descansos activos durante las horas de clase, los descansos y las lecciones antes y después. Este análisis se deriva de un examen exhaustivo de la literatura existente con respecto a la correlación entre el entorno escolar, la salud y la promoción preventiva de la salud, reconociendo la naturaleza continua del problema y la necesidad de una mayor contemplación para alinearse con los cambios futuros.Palabras clave: actividad física, fisiología, escuela.Abstract. The school context embodies the optimal environment for educating children towards the adoption of active lifestyles. This is auspicious not only in terms of physical health but also from a psycho-pedagogical and social standpoint. The need to integrate physical activity into the school routine, particularly in primary education, where behaviors are established and carried on into later stages of life, emerges clearly from the scientific literature. Health education sessions with a focus on preventive measures can be organized by the school’s medical services for the benefit of students. It is imperative within educational practices to view the motor domain as a crucial instrument for instilling appropriate lifestyles, enhancing cognitive growth, fostering inclusivity, and addressing psycho-emotional and socio-relational aspects. The school environment can significantly contribute by serving as a pivotal setting for promoting physical activity throughout various periods of the day. Movement can be incorporated into teaching activities, and active breaks can be integrated into class hours, either before or after lessons. This study stems from a comprehensive examination of the existing literature regarding the correlation between the school environment, health, and preventive health promotion. It recognizes the ongoing nature of the issue and the need for further investigation to align with forthcoming changes.Keywords: physical activity, physiology, school.